Auto‐tuning network for phased‐array high‐intensity focused ultrasound system. Issue 21 (1st October 2018) - Wang, Xusheng; Zhang, Ming; Rodes, Francis; Cao, Congjun
Abstract : In this Letter, an auto‐tuning system based on a variable synchronous switched capacitor is proposed for a phased‐array high‐intensity focused ultrasound system. The proposed system can automatically compensate the reactive power and impedance drift of each transducer caused by manufacturing tolerances and temperature variations. In contrast to traditional solutions, this system does not require measuring the impedances of each transducer or need microcontroller units to calculate the switch control signals. Furthermore, by using an air‐core inductor rather than a ferromagnetic‐core inductor in the auto‐tuning system, it naturally complies with the magnetic resonance imaging compatibility regulations.